Focal lesion of the right cingulum: a case report in a child. Issue 4 (April 1981) - Angelini, L; Mazzucchi, A; Picciotto, F; Nardocci, N; Broggi, G
Abstract : A body with a focal lesion of the right cingulum, subjected to cingulectomy for the removal of a tumour, is the first case of an isolated unilateral cingulum lesion to be reported. The presenting symptoms consisted of serious behavioural abnormalities: lack of social restraint, heightened sexuality, bulimia and aggressiveness, all of which ceased after surgery. Neuropsychological tests, done before and after the operation, provided no evidence that the higher cognitive functions, including memory, were impaired.